2019
DOI: 10.1039/c9nj02118c
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen reduction reaction mechanism on a phosporus-doped pyrolyzed graphitic Fe/N/C catalyst

Abstract: The interaction between neighbouring FeN4 and Psubs sites of a P-doped pyrolyzed Fe/N/C catalyst promotes four-electron reduction through associative and dissociative mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 94 publications
2
22
0
Order By: Relevance
“…In the interior of the graphene sheet, the FeN 4 active site prefers to adsorb the O 2 molecule with an endon configuration. 15,26,52 However, as reported by Ma et al, the presence of the FeN 4 site in the proximity of the graphitic edge makes the O 2 side-on adsorption configuration become more favorable. 9 The formation of O 2 side-on adsorption configuration on the transition-metal-N x site is often assumed to facilitate the ORR through the dissociative reduction pathway in the interior or at the edge of graphitic-like structures due to the significant elongation in the O−O bond of the adsorbed O 2 molecule.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…In the interior of the graphene sheet, the FeN 4 active site prefers to adsorb the O 2 molecule with an endon configuration. 15,26,52 However, as reported by Ma et al, the presence of the FeN 4 site in the proximity of the graphitic edge makes the O 2 side-on adsorption configuration become more favorable. 9 The formation of O 2 side-on adsorption configuration on the transition-metal-N x site is often assumed to facilitate the ORR through the dissociative reduction pathway in the interior or at the edge of graphitic-like structures due to the significant elongation in the O−O bond of the adsorbed O 2 molecule.…”
Section: Resultsmentioning
confidence: 86%
“…In our previous studies, we found that the inclusion of defects and doping does not significantly alter the ORR free energy profile for the associative mechanism since the O 2 adsorption properties on the FeN 4 site remain the same. 26,30,31 However, such a trend is not applicable when the FeN 4 site is located at the edge of ZGNR and AGNR. As we have observed in the previous subsection, the energetical preference for the O 2 adsorption configuration on the FeN 4 site becomes dependent on the graphene edge type and the FeN 4 orientation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, to simplify the procedure, we calculated the adsorption energies of the oxygen intermediates using a metal atom as the active site. However, for the materials doped with low-electronegativity heteroatoms, such as P, the oxygen may adsorb on the heteroatom rather than on the metal atom, thereby stabilizing the structure ( Dipojono et al, 2019 ). In addition, as the applied potential increases, the oxygen intermediates can be poisoned at the active site, resulting in different adsorption configurations as well as different ORR mechanisms ( Li et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%